2007
DOI: 10.1111/j.1398-9995.2007.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of symptoms of asthma, rhinitis and eczema in 13‐ to 14‐year‐old children in Africa: the International Study of Asthma and Allergies in Childhood Phase III

Abstract: Phase I of the International Study of Asthma and Allergies in Childhood has provided valuable information regarding international prevalence patterns and potential risk factors in the development of asthma, allergic rhinoconjunctivitis and eczema. However, in Phase I, only six African countries were involved (Algeria, Tunisia, Morocco, Kenya, South Africa and Ethiopia). Phase III, conducted 5–6 years later, enrolled 22 centres in 16 countries including the majority of the centres involved in Phase I and new ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
165
7
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(184 citation statements)
references
References 21 publications
11
165
7
1
Order By: Relevance
“…Polokwane, in the north of South Africa, participated in the ISAAC protocol, documenting a prevalence of both asthma and allergic rhinitis in this area almost as high as in Cape Town [12]. The most important result of this study is that it confirmed a high ongoing prevalence of allergic conditions in the north of South Africa.…”
Section: Prevalence Of Asthma In Southern Africasupporting
confidence: 67%
See 1 more Smart Citation
“…Polokwane, in the north of South Africa, participated in the ISAAC protocol, documenting a prevalence of both asthma and allergic rhinitis in this area almost as high as in Cape Town [12]. The most important result of this study is that it confirmed a high ongoing prevalence of allergic conditions in the north of South Africa.…”
Section: Prevalence Of Asthma In Southern Africasupporting
confidence: 67%
“…This means that we can use this together with the data from Cape Town, to suggest a prevalence for all of South Africa. The prevalence of asthma symptoms in Polokwane was 18%; not dissimilar to the 20,7% in Cape Town [12].…”
Section: Prevalence Of Asthma In Southern Africamentioning
confidence: 99%
“…17,31 The prevalence of asthma varies widely between countries: Ethiopia 9.1%, Kenya 15.8%, Nigeria 13.0%, Mozambique 13.3%, and South Africa 20.3%. 24,32 Asthma appears to be more severe in sub-Saharan Africa than in affluent countries, although the latter have the highest symptom prevalence. 32,33 In countries where several centres are involved in surveys, the prevalence of asthma is generally highest in urban areas.…”
Section: Prevalence Of Asthmamentioning
confidence: 99%
“…In urban areas which have become increasingly 'westernised', the prevalence is higher and is similar to European countries. 24 Owing to the projected increase in the urban population in sub-Saharan Africa, it is estimated that there may be an increase of at least 35% in the number of people with asthma by 2025. 21 In developed countries children under the age of 15 years represent approximately 20% of the population, whereas in sub-Saharan Africa these children form approximately half of the population.…”
Section: Prevalence Of Asthmamentioning
confidence: 99%
See 1 more Smart Citation